2014
DOI: 10.1002/pc.23344
|View full text |Cite
|
Sign up to set email alerts
|

Highly filled graphene‐benzoxazine composites as bipolar plates in fuel cell applications

Abstract: This research emphasizes on the development of highly filled graphene-polybenzoxazine composites and investigates thermal, electrical, and mechanical properties of the obtained composites for bipolar plate applications. The composition of graphene loading was achieved to be in the range of 10-60 wt%. The experimental results revealed that at the maximum graphene content of 60 wt% (44.8 vol%) in the polybenzoxazine, storage moduli at room temperature of the composites were considerably enhanced with the amount … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 45 publications
4
38
1
Order By: Relevance
“…T g values of the specimens were 200, 203, 206, 208, and 209 °C having graphene content ranging from 0 to 10 wt %. These findings were higher than the T g value of 174 °C reported for the neat PBA . The maximum T g value was 209 °C at the sample having 10 wt % of graphene which was 35 °C higher than the graphite‐filled PBA matrix.…”
Section: Resultscontrasting
confidence: 63%
See 2 more Smart Citations
“…T g values of the specimens were 200, 203, 206, 208, and 209 °C having graphene content ranging from 0 to 10 wt %. These findings were higher than the T g value of 174 °C reported for the neat PBA . The maximum T g value was 209 °C at the sample having 10 wt % of graphene which was 35 °C higher than the graphite‐filled PBA matrix.…”
Section: Resultscontrasting
confidence: 63%
“…The results indicated that graphene acted as catalyst for oxazine ring‐opening polymerization thus accelerated the curing behavior of BA‐a network as observed by Plengudomkit et al . in a previous study . Such finding could be attributed to the appearance of carboxyl group attached on the graphene which was naturally presented during typical graphene synthesis as suggested in the technical data sheet of graphene nanoplatelets‐grade H from XG Sciences .…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…The determination of density can provide insight into the nature of the particle dispersion within the polymer matrix as well as the presence of voids or air gap formation in the sample . One of the outstanding characteristics of BA‐a is low A‐stage viscosity and therefore, it provides good filler wetting characteristic and allows large amount of filler or reinforcement to be incorporated in the matrix resin during composite fabrication as previously reported . As expected in nanosilica‐filled poly(BA‐a) composites, the measured densities of the poly(BA‐a) composites filled with hydrophilic nanosilica particles of 7, 14, 20, and 40 nm clearly exhibited a linear relationship with nanosilica contents following the rule of mixture as can be seen in Figure a.…”
Section: Resultsmentioning
confidence: 53%
“…Highly filled composite systems in polybenzoxazines were initiated in Prof. Ishida's laboratory more than 25 years ago especially for microelectronic packaging applications. Since then, several other highly filled composites based on polybenzoxazines for various interesting applications have been reported such as in high thermally conductive composites, wood substituted polybenzoxazine composites, bipolar plate composites, and friction wear . Typically, the polymer matrix, reinforcement, and the adhesion between the matrix resin and the filler are the key factors controlling properties of composite materials .…”
Section: Introductionmentioning
confidence: 99%